Systematization of Previous Studies on Climate Crisis and Childhood of Indigenous Peoples. Case of Guatemala - Reyna , Gustavo (2025)
Aware that international literature on the climate crisis and childhood is vast worldwide, its relationship with Indigenous peoples remains limited. Considering that its effects are disastrous in urban areas, they can be even more devastating in rural regions, especially for Indigenous children. In this regard, we believe that more research should be conducted with this approach. For this study, we have tracked and documented 80 publications of various affiliations and critically and meaningfully analyzed 36 ad hoc references aligned with our objective: to develop a systematized document containing information from the last ten years that serves as a basis for constructing differentiated indicators within the framework of the climate crisis and its effects on Indigenous childhood in Guatemala and beyond. Additionally, specific objectives include: Systematizing and analyzing information from the tracking of 80 references and further examining 36 selected references. Organizing and assessing information based on economic sectors addressed in various studies, the geographical locations of the reviewed research, and the diverse sectors examined. We employed a qualitative methodology with documentary analysis and descriptive statistics. We conclude that studies on this specific issue in Guatemala remain scarce. Therefore, it is necessary to investigate the impact of the climate crisis on Indigenous childhood through field research, based on previous studies, to contribute to fostering further research aimed at finding solutions for its effects on health, education, gender, and nutrition among Indigenous children.